Hot dance fever. Vol. 1. (Able Music International Inc)
[1.] All rise. -- [2]. I like. -- [3]. Sexy. -- [4]. I'm a slave for you. -- [5]. Whenever, wherever. -- [6]. Overprotected. -- [7]. Can't get you out of my head. -- [8]. Get the party started. -- [9]. Move it like this. -- [10]. Nasty girl. -- [11]. Angelina. -- [12]. Gentlemen. -- [13]. Everything. -- [14]. Too close. -- [15]. It's raining men. -- [16]. Lady Marmalade.
Keywords: Disco